Analisis Faktor – Faktor yang Mempengaruhi Keputusan Pembelian dalam Penggunaan Jasa Pengiriman - Abdur Rohim; Eman Sulaiman (Universitas Negeri Padang, 2020)
Based on the results of research and a discussion of the factors that influence consumers to use JNE's delivery services Ampera Bekasi Timur Agent, then from the things that the authors can make the conclusion of the research results, namely: self-belief and attitude, lifestyle, family and knowledge, are factors which influenced the purchase decision to use the delivery service of JNE Agent Ampera Bekasi Timur. The factors obtained in this study can influence consumers in using JNE Ampera Bekasi Timur Bekasi agent delivery services by 60.602%. That is, the factors formed are considered to influence the purchase decision to use the JNE Ampera Agent Bekasi Timur delivery service. The dominant factors affecting purchasing decisions in East Bekasi Ampera Agent JNE delivery services are personality and self-concept factors because they have the highest eigenvalues value or are able to explain the decision process to use JNE shipping services for East Bekasi Ampera Agent of 36.524% or greater than the three other formed factors.